Bulk metallic glasses based on precious metals: Thermal treatments and mechanical properties. (August 2015) - Cardinal, S.; Qiao, J.; Pelletier, J.M.; Kato, H.
Abstract: The thermomechanical behavior of precious based metallic glasses has been investigated. Their compositions are free of nickel for biocompatibility. The gold-based BMG has a gold content resulting in 18 Karats alloy, a supercooled liquid region of 43 °C and a casting diameter up to 5 mm in rod. The compositions of platinum and palladium based BMGs are interesting as they can be formed into bulk glassy rods with diameter up to 15 and 30 mm respectively. The platinum-based BMG has a platinum content resulting in 850 Pt grade with a supercooling region reaching 58 °C. The palladium-based BMG is principally composed of 40 wt.% palladium and 32 wt.% platinum, with a large supercooling region reaching 73 °C. The thermoplastic deformation of these BMG has been examined using thermomechanical analyser (TMA) and the results show that the alloys can be easily processed in the supercooled liquid region. During thermal processing, crystallization must be controlled since it improves hardness and elastic modulus, but embrittles the alloys and stops the deformation. The high hardness of Au-, Pt- and Pd- base BMGs (respectively 340, 420, 460 HV) twice the value of conventional precious metals, coupled with good properties for superplastic forming in the supercooled liquid region made them promising materials for watch making and jewelry applications. Highlights: Crystallization in Au-, Pt- and Pd-based BMGs was studied by XRD, TMA and hardness. Coherent information on the influence of temperature and time are obtained. Processability of Pd- and Pt-is very good, that of the Au-base BMG is much lower. A large supercooled liquid region is crucial for thermo-plastic processing.